MEMBANGUN PERIKANAN PERAIRAN UMUM BERBASIS KEARIFAN LOKAL - M. Nasyiruddin Arsyad; Elok Ilunanwati; Akbar Saefudin (University of PGRI Palembang, 2003)
Environment degradation and irrational fishing pushed the riverine fisheries resources in South Sumatra in critical condition. Eventhough government rules on fishing activity was established, it was not supported by law supermation in the field. On the other hand, water resources management called lelang lebak lebung has been established and practiced by the local people. This study tried up to describe and analyze the local knowledge on water resources management and suggested some alternatives to its development.Keywords : riverin fisheries, government rules, local people, local knowledge